Cord Blood Alkaline Phosphatase Level as a Predictor for Neonatal Jaundice in Healthy Term Newborns - Vishnu Priyaa Rajasegaran; Preethi Tamilarasan; Bharath Kumar Thirunavukkarasu (Journal of Pediatrics Review)
Background: Neonatal hyperbilirubinemia is one of the common and benign conditions occurring in 80% of preterm and 60% of term neonates during their first week of life. Though most cases are physiological and usually resolved without treatment, it is crucial to identify at-risk neonates of developing severe hyperbilirubinemia so that therapeutic intervention can be initiated sooner to prevent long-term morbidity. As a result, an early assessment of the risk for hyperbilirubinemia is crucial, as most healthy neonates are discharged early. Objectives: This study aimed to compare cord blood alkaline phosphatase (ALP) levels between jaundiced and non-jaundiced neonates and to correlate the cord blood ALP levels with serum bilirubin levels in newborns with neonatal jaundice. Methods: A hospital-based prospective cohort study was conducted on 126 healthy term newborns born to mothers without risk factors. Umbilical cord blood ALP was measured in all neonates. Then, the neonates were followed up daily for clinical jaundice for up to 3 days of life. They were subjected to further blood investigations if found icteric. Results: This study showed a statistically significant correlation between the cord blood ALP level and the development of clinical jaundice. The median ALP level was also high in neonates who had clinical jaundice requiring phototherapy. According to the receiver operating curve (ROC), the most suitable cut-off value for cord blood ALP level for predicting neonatal jaundice with a sensitivity of 52%, specificity of 66%, positive predictive value of 60.47%, negative predictive value of 57.89%, and diagnostic accuracy of 59% was found to be more than 147 IU/L. The area under curve value for cord blood ALP was 0.665, which was satisfactory. Conclusions: Cord blood ALP can be taken as a reliable marker in healthy term neonates to predict the risk of significant hyperbilirubinemia and the need for phototherapy despite having low sensitivity and specificity in this study.